Identification of Streptococcus intermedius and Stenotrophomonas maltophilia in recurrent leucorrhoea: a case report - Marselinus Edwin Widyanto Daniwijaya; Atthobari; Ade Christanti Putri Sidabutar; Devi Artami Susetiati; Titik Nuryastuti (Journal of Clinical Microbiology and Infectious Diseases, 2021)
Introduction: Leucorrhoea or fluor albus a whitish vaginal discharge is commonly found in reproductive women with familiar symptoms such as itching, with or without distinctive odor. Several factors are responsible for leucorrhoea including infectious and non-infectious factors. Streptococcus intermedius and Stenotrophomonas maltophilia are bacteria that cause infections that are rarely found in vaginal discharge. Case description: A 23-year-old woman, with a history of recurrent vaginal discharge, presented herself in the outpatient clinic dermatology and venereology RSUP Dr. Sardjito, with the main complaint of vaginal discharge. On the previous visit to the outpatient clinic, she was diagnosed with vulvovaginal candidiasis and received Azithromycin, ketoconazole.  Microbiology culture of the vaginal swab results in two bacterial infections Streptococcus intermedius and Stenotrophomonas maltophilia. Conclusion: A rare finding on the identification of Streptococcus intermedius and Stenotrophomonas maltophilia in outpatients with recurrent leucorrhoea. These findings suggest that Streptococcus intermedius and Stenotrophomonas maltophilia which is an uncommon profile of microorganism could also be assumed to be involved in recurrent leucorrhoea in this case report. Other pathogenic organisms should be considered since there limitation in the identification process in diagnostic of the patient.